(untitled) (Medico Legal Update, 2019)
Various cephalofacial measurements are helpful to establish human identity with respect to sex, race, stature etc. The objective of this study is documenting the craniofacial traits and sex differences with respect to Cephalic Index of Tamil population. Maximum breadth and length of human head are measured in subjects comprising of 100 males and 100 females in the age group of 18-23 years. The mean Cephalic Index calculated based on above metric data for males and females comes to 77.93 ± 5.10 and 75.22 ± 2.92 respectively. As per our findings, the predominant head shape of the study subjects in Tamil population is Mesocephalic for both sexes.